ALIH KODE CAMPUR KODE DALAM FILM “PR-KU MUNG KOWE” DI YOUTUBE BATS CHANNEL - Ritasari, Siska Dina; Firnanda, Reyza (Jurnal Online Baradha, 2024)
Language variations are often found in people's daily conversations. Language variation arises when a society has diverse languages. Language variation is a variation or variety of language according to its use. In language variations discussing code switching and code mixing, code switching is the event of using one code to another. There are two forms, namely internal (inner) code switching and external (outer) code switching. Meanwhile, code mixing is the process of inserting regional languages or other foreign languages. There are two forms, namely positive and negative code mixing. Data and data sources are from the film "PR-Ku Mung Kowe" on the YouTube Bats channel. The method used in this research is descriptive qualitative. The data collection technique for this research consists of two parts, namely the method of listening to the film "PRKu Mung Kowe" and the note-taking method. The results of the discussion found were forms of internal and external code switching and negative forms of code mixing in the film "PR-Ku Mung Kowe" aimed at creating a society that is good and correct in language. Keywords : language variations, code switching, code mixing